Harder, better, faster, stronger? Mental toughness, the dark triad and physical activity - Vaughan, R.; Carter, G. L.; Cockroft, D.; Maggiorini, L. (Personality and Individual Differences, 2018)
Mental toughness (MT) provides additional psychological resources important for achievement and health outcomes in sport. Previous research has highlighted complex relationships between the Dark Triad (DT; sub-clinical narcissism, Machiavellianism, and psychopathy) and MT, but with little focus on health-related behaviours - i.e., physical activity (PA). The aim of this study was twofold: to assess the relationship between these variables and determine any differences as a function of athlete expertise; and, to determine whether MT mediated the DT-PA relationship, and whether this relationship differed across athlete expertise. In total, 762 participants with varying levels of sports participation experience - elite (n = 222), amateur (n = 338), and non-athletes (n = 202) - completed questionnaires assessing DT, MT, and PA. Results indicated that elite athletes scored higher on all variables compared with amateur athletes who in turn scored higher than non-athletes. Moreover, positive relationships were found between narcissism and MT. Structural equation modelling indicated MT fully mediated the relationship between DT and PA, and this effect was more evident for elites and amateurs than non-athletes.